Identification of root-associated arbuscular mycorrhizal fungi in cassava (Manihot esculenta Crantz) in Manokwari Regency, West Papua, Indonesia - Antonius Suparno; Darmawanta Tarigan; Yohanis Amos Mustamu; Linda Ernawati Lindongi; Wiwik Hardaningsih (Jurnal Ilmiah Pertanian, 2023)
Arbuscular mycorrhizal fungi (AMF) are crucial for plants growing on marginal soils, especially those with a very high dependence on AMF; one of them is plants with few roots, such as cassava. This study aimed to identify the AMF associated with cassava in six locations in Manokwari Regency, West Papua, Indonesia. The research was carried out using an observation method and purposive sampling at 6 locations. Soil samples were taken from the rhizosphere of 8-month-old cassava plants, with 2 kg of soil at each site. Furthermore, using the host plant Sorghum bicolor L, AMF was trapped in rhizosphere soil samples for three months. The spore morphology identification showed that cassava in North Manokwari District was associated with 3 genera 7 species, West Manokwari District-Manggoapi obtained 3 genera 7 species, Warmare District obtained 2 genera 7 species, Prafi SP-3 District obtained 3 genera 6 species, Masni SP-5 District obtained 3 genera 7 species, and Masni SP-8 District obtained 2 genera 7 species. The highest AMF colonization rate (94%) was found in the roots of the host plant Sorghum bicolor (L.) originating from Masni SP-5 District with the AMF composition consisting of Acaulospora cf. rehmi, Acaulospora cf. spinosa, Acaulospora cf. gerdemanii, Glomus cf. clarum, Gigaspora cf. margarita, Gigaspora cf. rosea, and Gigaspora cf. gigantea.